Miejsce i przestrzeń w edukacji na przykładzie działań w Szkole Podstawowej nr 82 we Wrocławiu - Czerwińska-Górz, Bożena; Muszyńska, Joanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article shows the meaning of place and space in the education process of children and youths. These issues can be perceived in many different ways, including, among others, as living and learning space of a youth. The text describes the process of core curriculum implementation and introducing culture through widely understood classes outside school buildings. What a child experiences and learns in an unconventional way has a huge influence on him or her and enables them easier acquisition of curriculum content. At the same time it helps to shape a child’s cultural identity as well as develop interests and abilities. It also gives a teacher the possibility of a closer contact with a student and enables to discover their individual predispositions.
Keywords: place; space; education; core curriculum; primary school; cultural education